Learning from old practices and local farmers to improve and assure rootstock quality of Nagpur mandarin saplings: Performance of Nagpur mandarin buds on Rangpur lime (C. limonia) and Rough lemon (C. jambhiri) rootstock - Sthapit, B.; Hom, S.; Singh, I.P.; Ramanatha Rao, V.; Lamers, H. (2012)
This flyer gives good insight into the value of mother tree maintenance for a specific rootstock, how it is maintained and used successfully in the field, how it contributes to the livelihoods and well-being of many rural households. The ‘Conservation and Sustainable Use of Cultivated and Wild Tropical Fruit Diversity: Promoting Sustainable Livelihoods, Food Security and Ecosystem Services’ project identified the efforts and role of these innovative nurserymen as a good practice of diversity management that is selected for further strengthening and scaling up within the community and elsewhere.